Antitrust risk in EU manufacturing: A sector-level ranking - Mario Mariniello; Marco Antonielli (Bruegel, 2014)
Based on a dataset of manufacturing sectors from five major European economies (France, Germany, Italy, Spain and the United Kingdom) between 2000 and 2011, we identify a number of key sector-level features that, according to established economic research, have a positive impact on the likelihood of collusion. Each feature is proxied by an "Antitrust Risk Indicator" (ARI). We rank the sectors according to their ARI scores. At 2-digit level, sectors that appears more exposed to collusion risk are those that tend to score high in most of the ARIs: Tobacco, Pharmaceuticals, Beverages, Chemicals. The 4-digit analysis suggests higher anticompetitive risk in Tobacco products, Spirits, Sugar, Railway Locomotives and Aircraft (high concentration and fixed costs), Coating of Metals and Printing (low import penetration), Tobacco products, Meat products, Footwear and Clothing (high market stability), Plastic products and Spinning/Weaving of textiles (high symmetry of market leaders). We then rank sectors according to the distribution of antitrust intervention by the European Commission between 2000 and 2013, in terms of merger control and anti-cartel enforcement. Tobacco, Paper and paper products, Pharmaceuticals and Food products are the sectors for which a notified merger has a greater likelihood of being deemed problematic by the Commission. There has been a greater incidence of anti-cartel action in Chemicals, Tobacco, Beverages, Electric equipment and Rubber and plastic. Antitrust investigations are based on the identification of narrow product markets. The characteristics of these markets are not necessarily well represented by average measures at sector level. Nevertheless, a simple comparison exercise shows that the European Commission's interventions have been largely consistent with sector rankings based on market concentration.
Keywords: 330